Can paramedics use FRAX (the WHO Fracture Risk Assessment Tool) to help GPs improve future fracture risk in patients who fall? Protocol for a randomised controlled feasibility study. Issue 9 (3rd September 2014) - Clarke, Shane; Bradley, Rachel; Simmonds, Bethany; Salisbury, Chris; Benger, Jonathan; Marques, Elsa; Greenwood, Rosemary; Shepstone, Lee; Robinson, Maria; Appleby-Fleming, John; Gooberman-Hill, Rachael
Abstract : Introduction: Currently identification, and therefore, management of patients at risk of osteoporotic fracture in the UK is suboptimal. As the majority of patients who fracture have fallen, it follows that people who fall can usefully be targeted in any programme that aims to reduce osteoporotic fracture. Targeting vulnerable patients who are likely to benefit from intervention may help shift the management of fracture prevention into primary care, away from emergency departments. Paramedics who attend to patients who have fallen may be well placed to assess future fracture risk, using the Fracture Risk Assessment Tool (FRAX) and communicate that information directly to general practitioners (GPs). Methods and analysis: This feasibility study takes the form of a pragmatic, randomised controlled trial aimed at exploring and refining issues of study design, recruitment, retention, sample size and acceptability preceding a large-scale study with fracture as the end point. Patients (aged >50) who fall, call an ambulance, are attended by a study paramedic and give verbal consent will be asked FRAX and fall questions. Patients who subsequently formally consent to participation will be randomised to control (usual care) or intervention groups. Intervention will constitute transmission of calculated future fracture risk to the patients' GP with suitable, evidence-based recommendations for investigation or treatment. 3 months after the index fall, data (proportion of patients in each group undergoing investigation or starting new treatment, quality of life and health economic) will be collected and analysed using descriptive statistics. A nested qualitative study will explore issues of acceptability and study design with patients, paramedics and GPs. Ethics and dissemination: This protocol was approved by NRES Committee South Central Oxford C in October 2012. Research Ethics Committee ref.12/SC/0604. The study findings will be disseminated through peer-reviewed journals, conference presentations and local public events. A publication plan and authorship criteria have been preagreed. Trial registration number: ISRCTN: 36245726.